Comparison of Clinical Methods With the Faecal Gluten Immunogenic Peptide to Assess Gluten Intake in Coeliac Disease. Issue 3 (September 2018) - Gerasimidis, Konstantinos; Zafeiropoulou, Konstantina; Mackinder, Mary; Ijaz, Umer Z; Duncan, Hazel; Buchanan, Elaine; Cardigan, Tracey; Edwards, Christine A.; McGrogan, Paraic; Russell, Richard K.
ABSTRACT: Objectives: Detection of faecal gluten immunogenic peptides (GIP) is a biomarker of recent gluten consumption. GIP levels can be used to monitor gluten intake and compliment clinical methods to evaluate compliance to gluten-free diet (GFD). In the present study, recent gluten intake was measured by GIP in children with coeliac disease (CD) and compared to routine clinical measures to evaluate GFD compliance. Methods: GIP was measured in 90 samples from 63 CD children (44 previously and 19 newly diagnosed with follow-up samples at 6 and 12 months on GFD). Compliance to GFD was evaluated based on clinical assessment, tissue transglutaminase (tTG) levels, and Biagi score. Results: GIP was detectable in 16% of patients with previous CD diagnosis on GFD. Body mass index z score ( P = 0.774), height z score ( P = 0.723), haemoglobin concentration ( P = 0.233), age ( P = 0.448), sex ( P = 0.734), or disease duration ( P = 0.488) did not differ between those with detectable and nondetectable GIP. In newly diagnosed patients, on gluten-containing diet, GIP was detectable in 95% of them. Following GFD initiation, GIP decreased ( P < 0.001); 17% and 27% had detectable levels at 6 and 12 months, respectively. Compared to GIP, the Biagi score, tTG, and clinical assessment presented sensitivity of 17%, 42%, and 17%, respectively. Likewise, GIP was detectable in 16%, 16%, and 14% of patients evaluated as GFD compliant according to the Biagi score, tTG, and clinical assessment, respectively. A combination of methods did not improve identification of patients who were noncompliant. Conclusions: Inclusion of faecal GIP measurements is likely to improve identification of GFD recent noncompliance in CD management and could be incorporated into current follow-up strategies. Abstract : Supplemental Digital Content is available in the text